Faktor-Faktor yang Berhubungan dengan Perilaku Cuci Tangan Pakai Sabun dalam Masa Pademi Covid-19 pada Siswa/i SMP - Rina Oktavia; Andriyani; Triana Srisantyorini; Ernyasih (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Based on the results of the Banten Province Basic Health Research, the hand washing behavior of the people in the 10-14year age group in Banten Province is 42%, and in the school children group, it is 44.5%. In South Tangerang City, the proportion of good and correct handwashing behavior in 2018 was 69.12%. Public awareness in carrying out hand washing behavior is still low. This study aims to determine the factors related to washing hands with soap during the Covid-19 pandemic—a cross-sectional design with a sample of 172 class VIII students. The sampling technique used was purposive sampling. Data analysis with Chi-Square (α = 0.005). Respondents with good Hand Washing Behavior with Soap or “Cuci Tangan Pakai Sabun” (CTPS) were 85.5%. Female respondents are 51.2%, have good knowledge of CTPS (62.2%), have good CTPS attitudes (64%), have peer support (50.6%), and have good facilities and infrastructure adequate (89%). There is a relationship between knowledge (p=0.024), attitude (p=0.013), facilities and infrastructure (p=0.009), and age (p=0.000) with the behavior of washing hands with soap. There is no relationship between gender and peer support with the conduct of washing hands with soap. The factors related to the behavior of washing hands with soap in students at SMP Negeri 6 Tangerang Selatan City are age, knowledge, attitudes, and facilities and infrastructure. The suggestion is to cooperate between the school and related parties to provide counseling about the behavior of washing hands with soap so that students can apply their knowledge and attitudes in everyday life.